Effect of Cultural-Based Breast Self-Examination Educational Program on BSE Self Efficacy Among Nursing Student, Indonesia - Juanita Juanita; Piyanuch Jittanoon; Umaporn Boonyasopun (The Faculty of Veterinary Medicine of Syiah Kuala University, 2020)
The clinical breast self-examination is one of the strategies to prevent breast cancer to women. Previous study was conducting to promote breast self-examination, but the study did not consider about the role of culture on health behavior. The purpose of this quasi-experimental design was to examine the effect of cultural-based breast self-examination (BSE) educational program on BSE self-efficacy among nursing students. The cultural-based BSE educational program was developed based on Bandura’s Social Cognitive Theory and Islamic Culture. A stratified proportionate random sampling method was employed to recruit nursing students at Public Nursing College, Faculty of Medicine, Syiah Kuala University in Aceh, Indonesia. Seventy-six students who met the inclusion criteria were recruited, 36 students were in the experimental group and 40 students were in the control group. The experimental group received the cultural-based BSE educational program including exploring Islamic mandate on prevention and individual responsibility in health promotion and cultural related beliefs toward BSE, health education, BSE training, and follow-up. The BSE self-efficacy scores were examined after 3 weeks of program implementation. The statistical analysis was conducted using dependent t-test and independent t-test. The results showed, the BSE self- efficacy of the nursing students in the experimental group were significantly higher than before participation ( t (35) =-5.02, p .001). Further, the BSE self-efficacy score in the experimental group was significantly higher than thecontrol group after participation the program (t (74) = 3.49, p .01). The result showed differences of the overall BSE self-efficacy and the subscale: BSE procedural efficacy (p .01), but not significant differences for the subscale: BSE barrier management efficacy (p .05). The cultural-based BSE educational program is effective in enhancing BSE self-efficacy among nursing students. The study suggests that the application of the cultural-based BSE educational program would be extended for other women and other nursing students in different areas.